PENGEMBANGAN KONSEP AREA INDUSTRI KOPI BERBASIS TEACHING FACTORY MELALUI VISUALISASI 3D ENVIRONMENT MODELING - Prihartini, Narti; Milda Surgani Firdania; Fiqih Akbari (PPPM POLTESA, 2023)
Politeknik Negeri Sambas has initiated the development of teaching factory directed to the plantation agribusiness sector with a focus on the downstream phase of coffee agribusiness. To support this initiation, infrastructure on production and research laboratories are needed in the processing of industrial products and be able to increase research based on the output of innovative products. Several things that need to be prepared to support the development of a teaching factory-based coffee industry area in Sambas Regency include preparing a coffee industry center with supporting infrastructure in the form of a research laboratory and coffee processing machines which are visualized in the form of 3D Environment Modeling to provide a digital brief of the coffee industry area that can be used to check the feasibility of developing an area, the 3D Environment Modeling concept can be applied in both interior and exterior contexts. The results of the design are visualized in the form of a 3D Environment Modeling Animation Video of the coffee industry area in MP4 format and archived in DVD. Through this concept, it can provide an insight to stakeholders and the Politeknik Negeri Sambas community about the feasibility of developing a teaching factory-based coffee industry area in Sambas Regency.